ANALISIS KUALITAS LAYANAN WEBSITE PROGRAM STUDI SISTEM INFORMASI MENGGUNAKAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Fuad Rafi Khamdani; Ito Setiawan (JURNAL REKAYASA SISTEM INDUSTRI, 2023)
The growing development of information technology makes information technology a very important resource for government and private organizations. The same applies to the university environment in student services. Amikom Purwokerto University is one of the many tertiary institutions that has implemented a web-based academic information system, including in one of its study programs, namely Information Systems. Based on interviews conducted by researchers with one of the lecturers in the Information Systems Study Program at Amikom University, Purwokerto, several problems were identified, such as the lack of regular updating of data and information on the website, the appearance of the website which was less attractive, and the lack of available content. Then, so that the company can be ready to compete with other similar websites, it is necessary to analyze the quality of the website, one of which is using the WebQual 4.0 method which is then assessed using the Importance Performance Analysis (IPA) method. The data were obtained by distributing questionnaires with 3 WebQual 4.0 variables based on the level of performance and the level of user expectations for the 85 samples that have been determined by calculating the Slovin formula. The data obtained is then assessed using the Importance Performance Analysis (IPA) method which produces recommendations to companies for actions that need to be taken on the website in order to improve and maintain the quality of the website. The results of the GAP analysis obtained 9 variables with positive values and 13 variables with negative values. While the results of the IPA analysis obtained variables that have been grouped into 4 quadrants, with 1 variable being the main priority, namely UQ8.